Pengembangan Aplikasi Sahabat Bunda | Cegah Stunting Berbasis Android Sebagai Upaya Pencegahan Dini Stunting - Selasih Putri Isnawati Hadi; Tri Budi Rahayu (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
The sustainability of a nation is undeniably determined by the quality of the nation's generation as its successor. One of the health problems arising in developing countries including Indonesia is stunting, a condition where children’s height is shorter than those of their age. The First 1000 Days of Life Priority is an effort carried out to prevent stunting, given that malnutrition in this golden period can be irreversible (cannot be recovered). This research aims to develop an android-based application as an effort of early prevention of stunting. This research is considered as a Research and Development (R&D) carried out by using the ADDIE method: Analysis, Design, Development, Implementation and Evaluation. Random sampling was employed and 19 mothers with toddlers aged 0-36 months in Patalan Village were chosen as samples with predetermined inclusion and exclusion criteria. A closed questionnaire was utilized as the research instrument to see the application’s feasibility based on the assessment carried out by material experts, media experts, and users. The questionnaire had been tested through validity judgment in advance. The average score of the media expert assessment was 100.66 (feasible category); the average score of the material expert assessment was 80.33 (feasible category); the average score of the small group trial was 110.5 (very feasible category); and the average score of the implementation was 111.5263 (very feasible category). This application is considered feasible for use because this application is informative, the language is easy to understand and it is regarded as easy to use by the users.